2022
DOI: 10.36834/cmej.73858
|View full text |Cite
|
Sign up to set email alerts
|

“R1 Nightmares”: a resident-led on-call medical emergency simulation course for junior residents

Abstract: Implication Statement On-call medical emergencies can be a source of anxiety for junior medical residents. Senior resident teachers are well-positioned to teach a safe approach to managing on-call emergencies, and simulation-based training has educational and patient safety advantages. We describe the implementation of a resident-facilitated, on-call emergency simulation course for first-year residents. The course was low-cost, time-efficient, increased residents’ self-rated comfort with acutely deteriorating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Erica McKenzie and team wrote, "R1 Nightmares": a resident-led on-call medical emergency simulation course for junior residents. 15 They described an on-call emergency simulation course aimed to reduce anxiety surrounding oncall medical emergencies for junior medical residents. The participants reported that the course increased their comfort with acutely deteriorating patients.…”
Section: You Should Try Thismentioning
confidence: 99%
“…Erica McKenzie and team wrote, "R1 Nightmares": a resident-led on-call medical emergency simulation course for junior residents. 15 They described an on-call emergency simulation course aimed to reduce anxiety surrounding oncall medical emergencies for junior medical residents. The participants reported that the course increased their comfort with acutely deteriorating patients.…”
Section: You Should Try Thismentioning
confidence: 99%